Energetic efficiency and energy requirements during first stage of lactation in crossbred cows - PURANIK, U K; SINGH, V P; NEMA, R K; TIWARI, D P (The Indian Journal of Animal Sciences, 2013)
The comparative performance of 2 genetic groups of cows (8 in each), viz. genetic group 1( JFL, 1/2 J x 1/4HF xÂ  1/4 G) and genetic group 2 ( FJL, 1/2 HF x 1/4 J x 1/4 G). was studied in terms of nutrient utilization and energetic efficiencies for milk production. DCP and TDN intakes/W 0 75 kg were significantly ( P